Mini-review. Perspective on biomass derived bio-oil valorization in Vietnam - Thuan, Huynh Minh; Long, Duong Thanh; Hung My, Nguyen Huynh; Quoc Binh, Phan Minh; Luong, Nguyen Huu (Vietnam Journal of Chemistry, 2017)
Various strategies for biomass derived bio-oil valorization as a renewable feedstock for chemicals and fuels are described. Starting from the role of renewable resources (e.g. biomass, bio-oil) in the future energy and chemical community, an overview on current energy supply situation and the role of biomass and related products are discussed. Later, summary of bio-oil production from biomass and the need for upgrading to further uses is represented. Subsequently, the valorization of bio-oil as fuels and feedstocks are intensively summarized, showing the potential utilization of bio-oils via such processes. Some studies on biomass assessment, bio-oil production and upgrading in Vietnam are also given. Finally, some concluding remarks address the perspectives for further research and development to overcome future challenges. Keywords. Bio-oil valorization, bio-oil/diesel emulsion, co-feeding, deoxygenation, refinery units.